SUSTAINABLE DRIVERS OF FIRM VALUE: THE ROLE OF GREEN FINANCE, FINANCIAL PERFORMANCE AND ENVIRONMENTAL PERFORMANCE - farah; Busra, Busra (J-ISCAN: Journal of Islamic Accounting Research, 2025)
In the current era of sustainability, the influence of green finance on financial performance and firm value has become a strategic issue receiving considerable attention. Green finance is understood as a set of financial instruments designed to support environmentally friendly and sustainable activities. Its implementation not only generates positive impacts on environmental preservation but also has the potential to enhance a company’s economic aspects through improved operational efficiency, better risk management, and a stronger reputation among stakeholders. This study aims to analyze the effect of green finance, financial performance, and environmental performance on firm value in non-financial sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023. The independent variables include green finance (proxied by the PROPER score), financial performance (measured by Return on Assets/ROA), and market perception (represented by Tobin’s Q). The dependent variable is firm value, proxied by the Price to Book Value (PBV). Data were obtained from financial and sustainability reports of 10 purposively selected companies. The analysis was conducted using multiple linear regression with the assistance of SPSS software. The results show that both partially and simultaneously, ROA, PROPER, and Tobin’s Q have a significant positive effect on PBV. These findings indicate that sustainability practices and financial efficiency play a crucial role in enhancing a company's market valuation.